Design and Application of Annular Fuel Assembly for Small Reactor - JI Songtao, HE Xiaojun, ZOU Yuanfang, PAN Cuijie, SHI Xiaolei, DIAO Junhui, HU Liqiang, SHI Baolei, HAN Zhijie (Yuanzineng kexue jishu, 2023)
Small reactors have the characteristics of modular, short construction period and flexible deployment, which can serve as a clean distributed energy source not only for supplying power but also for meeting various needs such as seawater desalination, heating supply for both residence and industry. The double cladding of an annular fuel rod can significantly improve its heat transfer capacity. This characteristic is helpful for designing reactors with smaller core volume, higher core safety and better economy. It is believed that the application of annular fuel in small reactors can fully show its advantages, and meet the requirements of China’s nuclear energy development strategy. Based on low-temperature nuclear heating reactors, a scheme design of annular fuel assemblies for small reactors has been carried out, which mainly considered the influence of factors such as the height to diameter ratio of the core and the array of fuel rods. Physical analysis of different fuel assemblies design schemes were conducted by using the CMS code, and annular fuel assembly with a 11×11 array of fuel rods was ultimately designed. The annular fuel assembly used for small reactors mainly consists of bottom nozzle, top nozzle, fuel rods, guide tubes, and spacer grids, the primary structure design of annular fuel assembly was conducted based on results of the mechanical analysis. The feasibility of annular fuel assemblies applied to different types of small reactors was demonstrated by reactor physics analysis, thermal-hydraulic analysis and safety analysis. The radial power distribution factor, enthalpy rise factor, hot channel factor, moderator temperature coefficient, Doppler temperature coefficient and other parameters were analyzed by using the SIMULATE5 code, which meet the design requirements. The thermal-hydraulic performance, including distribution of velocity field, pressure field, and temperature field of annular fuel assemblies for low-temperature heating reactors was evaluated by using the CFX program, including distribution of velocity field, pressure field, and temperature field. For the small marine reactor, thermal-hydraulic analysis was carried out by using SAAF code, and the changes of fuel rod radial temperature distribution, heat flux, minimum DNBR and other parameters were obtained, the results show that annular fuel has a high safety margin. For cores loaded with different fuel assemblies, small break loss of coolant accidents was analyzed by using the RELAP5 code, the results show that the safety margin of annular fuel used for small reactor is large. In conclusion, annular fuel rod has a completely new structure design with superior heat transfer performance. The relevant analysis results indicate that annular fuel assembly has good prospect when applied in small reactors, it can further improve the safety and economy of small reactors.